2021
DOI: 10.14740/jh817
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of a Six-Week Treatment Course of Vitamin D2 and D3 in Children With Sickle Cell Anemia in Steady State With Hypovitaminosis D: A Randomized Clinical Trial

Abstract: Background Correction of vitamin D deficiency through administration of either vitamin D 2 or D 3 has been shown to reduce chronic bone pains and frequency of acute bone pains, increase bone density as well as improve growth stature in children with sickle cell anemia (SCA). Findings vary on the effectiveness of the two forms of the vitamin. The current study was carried out to compare the effectiveness of a 6-week treatment course of vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Initial research on pediatric SCD patients found that their risk of developing VDD is 5.3 times higher than that of healthy individuals (12). This has been supported by a recent study, which found that SCD patients had a five times higher risk of VDD than the general population (15,34). Further, children with SCD-SS were at higher risk for low vitamin D status in the spring season (35).…”
Section: Resultsmentioning
confidence: 58%
“…Initial research on pediatric SCD patients found that their risk of developing VDD is 5.3 times higher than that of healthy individuals (12). This has been supported by a recent study, which found that SCD patients had a five times higher risk of VDD than the general population (15,34). Further, children with SCD-SS were at higher risk for low vitamin D status in the spring season (35).…”
Section: Resultsmentioning
confidence: 58%
“…In recent years, studies of the relationship between 25(OH)D and anemia have focused on sickle cell anemia, and have demonstrated that 25(OH)D supplementation is helpful in treatment of sickle cell anemia [16,18,[21][22][23]; however, the overall relationship between 25(OH)D and anemia, particularly its trend, has not been clarified. Our study revealed a U-shaped relationship between serum 25(OH)D levels and risk of anemia, and with increased 25(OH)D level, hemoglobin level, and RBC counts the association showed a downward trend, suggesting that caution should be applied in the use of 25(OH)D supplementation to treat anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Might vitamin supplementation prevent or treat disease caused by parvovirus B19? A number of vitamin supplementation studies, most often with vitamin D, have been performed and have indicated benefit in patients with SCD, including a reduction in respiratory illness [73][74][75][76][77][78][79][80]. Nonetheless, study results have been mixed.…”
Section: Benefits/risks Of Vitamin Supplementationmentioning
confidence: 99%